Comparative Study of Brain fMRI of Olfactory Stimulation in Neuromyelitis Optica Spectrum Disease and Multiple Sclerosis - He, Shaoyue; Peng, Tingting; He, Weiwei; Gou, Chen; Hou, Changyue; Tan, Juan; Wang, Xiaoming (Frontiers in Neuroscience, 2022)
Objective: To observe the characteristics of brain fMRI during olfactory stimulation in patients with neuromyelitis optica spectrum disease (NMOSD) and multiple sclerosis (MS), compare the differences of brain functional activation areas between patients with NMOSD and MS, and explore the characteristics of olfactory-related brain networks of NMOSD and MS. Methods: Nineteen patients with NMOSD and 16 patients with MS who met the diagnostic criteria were recruited, and 19 healthy controls matched by sex and age were recruited. The olfactory function of all participants was assessed using the visual analog scale (VAS). Olfactory stimulation was alternately performed using a volatile body (lavender and rose solution) and the difference in brain activation was evaluated by task-taste fMRI scanning simultaneously. Results: Activation intensity was weaker in the NMOSD group than in the healthy controls, including the left rectus, right superior temporal gyrus, and left cuneus. The activation intensity was stronger for the NMOSD than the controls in the left insula and left middle frontal gyrus (P < 0.05). Activation intensity was weaker in the MS group than the healthy controls in the bilateral hippocampus, right parahippocampal gyrus, right insula, left rectus gyrus, and right precentral gyrus, and stronger in the left paracentral lobule among the MS than the controls (P < 0 05). Compared with the MS group, activation intensity in the NMOSD group was weaker in the right superior temporal gyrus and left paracentral lobule, while it was stronger among the NMOSD group in the bilateral insula, bilateral hippocampus, bilateral parahippocampal gyrus, left inferior orbital gyrus, left superior temporal gyrus, left putamen, and left middle frontal gyrus (P < 0.05). Conclusion: Olfactory-related brain networks are altered in both patients, and there are differences between their olfactory-related brain networks. It may provide a new reference index for the clinical differentiation and disease evaluation of NMOSD and MS. Moreover, further studies are needed.